Role Of Chewing Habits And Cigarette Smoking In Differentiation Of Oral Squamous Cell Carcinoma - Shumaila Younus; Naila Irum Hadi; Farah Ahmed; Haya Mohammad (ziauddin University, 2024)
Background: Oral squamous cell carcinoma (OSCC) is one of the most common cancers in the world. Cigarette smoking, gutka and pan are the most common addictions in Pakistan. This study is conducted to evaluate the frequency of these risk factors (cigarette smoking, gutka and pan) and correlate it with histopathological grade of OSCC.The objective of the study is to evaluate the role of cigarette smoking, gutka and pan consumption in the histopathological differentiation of Oral Squamous Cell Carcinoma. Methods: A cross-sectional study was conducted. OSCC patients (n= 138) were recruited through purposive sampling technique from Dental OPD of Ziauddin Dental College, Ziauddin Hospital, Karachi. A detailed questionnaire was filled with information regarding patient's medical history along with the daily consumption of cigarette, gutka and pan. Co-relations were studied between various continuous variables. Cross-tabulations were performed between frequency of habits and different histopathological grades of OSCC. Results: In the present study, 138 OSCC patients, 108 (78.3%) males and 30 (21.7 %) females, were enrolled and histopathologically diagnosed into well differentiated, moderately differentiated and poorly differentiated OSCC. Association of histopathological grades of OSCC with different age groups revealed moderately differentiated OSCC as the predominant histopathological differentiation in 30-39 years age group (46.3%). Majority of OSCC cases with cigarette smoking and gutka consumption used these products with frequency of > 15 packets per day, while, most of the pan consumers used 5-15 pan per day. All these patients had poorly differentiated OSCC i.e. 48.7% cigarette smokers, 64.1% gutka and 43% pan consumers. Conclusion: This study concludes that most of OSCC patients with habits of gutka, cigarette smoking and pan were associated with poorly differentiated carcinoma with more cases occurring in younger age group. This point to an alarming situation and se¬rious thought should be given to early detection and prevention. Key Words: Oral squamous cell carcinoma, frequency, cigarette smoking, gutka, pan, grading.